1995
DOI: 10.1002/jlb.57.1.72
|View full text |Cite
|
Sign up to set email alerts
|

The endoperoxides/TxA2 analogue, U46619, inhibits human polymorphonuclear leukocyte function

Abstract: The effects of the stable analogue of TxA2, U46619, on polymorphonuclear leukocyte (PMN) function were investigated. U46619, at micromolar concentrations, inhibited fMLP-stimulated aggregation, beta-glucuronidase release, and superoxide production. fMLP-induced LTB4 synthesis was also inhibited. U46619 did not modify intracellular Ca2+ increase induced by fMLP in Fura-2-loaded PMN, suggesting that early events of cell activation were not involved. In fact, U46619 also inhibited aggregation, beta-glucuronidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It has been proposed that TXA 2 modulates leukocyte function, based on observations of TXA 2 analogues enhancing the endothelial expression of adhesion molecules and chemokines (38,39), enhancing neutrophil migration (40), inhibiting neutrophil aggregation, ␤-glucuronidase release and superoxide production (41), and stimulating cytokine release from monocytes (42). In this report, we show that 11-dehydro-TXB 2 , a stable product of thromboxane metabolism, is an effective CRTH2 activator in human eosinophils and basophils, whereas the parent metabolite TXB 2 is inactive.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that TXA 2 modulates leukocyte function, based on observations of TXA 2 analogues enhancing the endothelial expression of adhesion molecules and chemokines (38,39), enhancing neutrophil migration (40), inhibiting neutrophil aggregation, ␤-glucuronidase release and superoxide production (41), and stimulating cytokine release from monocytes (42). In this report, we show that 11-dehydro-TXB 2 , a stable product of thromboxane metabolism, is an effective CRTH2 activator in human eosinophils and basophils, whereas the parent metabolite TXB 2 is inactive.…”
Section: Discussionmentioning
confidence: 99%
“…One may postulate that in the present study perfusion of the lung with U-46619 [and perhaps PGF 2␣ and PGI 2 (13,17,33,40)] may have acted on sequestered neutrophils, resulting in the generation of a respiratory burst and, ultimately, a neutrophil-mediated microvascular dysfunction (18,26). Other more recent studies have suggested that U-46619, as well as PGE 2 , PGF 2␣ , and PGI 2 , inhibits neutrophil activation, at least as manifested by increases in intracellular free calcium, leukoaggregation, and the release of superoxide radical, ␤-glucuronidase, and leukotriene B 4 (22,32,36). These more recent observations would appear to be inconsistent with the notion that U-46619 or PGE 2 , PGF 2␣ , or PGI 2 increased pulmonary microvascular permeability by activating on neutrophils sequestered within the lung.…”
Section: Discussionmentioning
confidence: 99%
“…U-46619 (9,11-dideoxy-11␣,9␣-epoxymethanoprostaglandin F 2␣ ) is a thromboxane-endoperoxide receptor agonist that has been commonly used to mimic the physiological effects of TxA 2 (4,22,23,25). The concentration of U-46619 was chosen based on a dose-response curve relating increasing concentrations of U-46619 to increases in K f in this experimental system (data not shown).…”
Section: Experimental Protocolmentioning
confidence: 99%